Intercalary reconstruction of long bones by massive allograft: Comparison of construct stability ensured by three different host-graft junctions and two types of fixations in a synthetic femur model - Baleani, Massimiliano; Erani, Paolo; Blaise, Manon; Fognani, Roberta; Palmas, Marco; Manfrini, Marco (Frontiers in Pediatrics, 2022)
An intercalary segmental allograft is an option for limb salvage in bone tumours. Stable and congruent intercalary reconstructions are a prerequisite for achieving host-graft union. However, a too rigid fixation could increase the risk of late complications correlated with negative bone remodelling. This study compared the reconstruction stiffness achieved by three different host-graft junctions, namely, end-to-end, modified step-cut, and taper. A low-stiffness bone plate was used as the fixation method, except for the taper junction where a low-stiffness intramedullary nail was also used to investigate the effects of different types of fixation on construct stiffness. Composite femora were tested under four loading conditions to determine coronal and sagittal bending stiffness, as well as torsional stiffness in opposite directions. Stiffness values were expressed as a percentage of intact host bone stiffness (%IBS). While a reduction of coronal bending stiffness was found with taper junctions (76%IBS) compared with the high values ensured by end-to-end (96%IBS) and modified step-cut junctions (92%IBS), taper junctions significantly increased stiffness under sagittal bending and torsion in intra- and extra-direction: end-to-end 29%IBS, 7%IBS, 7%IBS, modified step-cut 38%IBS, 20%IBS, 21%IBS, and taper junction 52%IBS, 55%IBS, 56%IBS, respectively. Construct stiffness with taper junctions was decreased by 11–41%IBS by replacing the bone plate with an intramedullary nail. Taper junctions can be an alternative to achieve intercalary reconstructions with more homogeneous and, in three out of four loading conditions, significantly higher construct stability without increasing bone plate stiffness. The risk of instability under high torsional loads increases when taper junctions are associated with a low-stiffness intramedullary nail.